2013
DOI: 10.1111/1365-2435.12099
|View full text |Cite
|
Sign up to set email alerts
|

Can plant–microbe–insect interactions enhance or inhibit the spread of invasive species?

Abstract: Summary 1.Invasive species are one of the great challenges facing the world leading to great economic losses. Increasing numbers of species introductions are also increasing the likelihood of new species interactions -particularly between plants, microbes and insects. 2. Frequently discovered interactions between plants, microbes and insects are giving rise to a new field: plant-microbe-insect (PMI) interactions. This paper focuses on novel PMI interactions created from the introduction of new plant, insect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 136 publications
1
22
0
Order By: Relevance
“…For the ERH, not only were initial similarity of the herbivore and the microbe to the plant significant factors in determining plant invasion success, but the interaction between microbe and herbivore was as well. This mirrors empirical studies that have found non-additive affects when investigating PMI interactions (Morris et al 2007;Bennett 2013). This is most likely related to the plant having a harder time invading because benefits gained from being similar to the microbe are canceled by the increased similarity to the herbivore under the BRH.…”
Section: Discussionsupporting
confidence: 75%
“…For the ERH, not only were initial similarity of the herbivore and the microbe to the plant significant factors in determining plant invasion success, but the interaction between microbe and herbivore was as well. This mirrors empirical studies that have found non-additive affects when investigating PMI interactions (Morris et al 2007;Bennett 2013). This is most likely related to the plant having a harder time invading because benefits gained from being similar to the microbe are canceled by the increased similarity to the herbivore under the BRH.…”
Section: Discussionsupporting
confidence: 75%
“…Many introduced species rely on multi‐trophic mutualisms in their new habitats to become naturalized (Traveset and Richardson ). Mutualisms can be important at all stages of the introduction‐naturalization‐invasion continuum: 1) for establishment via symbioses between plant roots and microbiota (Pringle et al , Dickie et al , Rodríguez‐Echeverría , Bennett ) or plant–ant protection (Ness et al ), 2) for reproduction via animal‐mediated pollination (Burns et al ), and 3) for dispersal via animal seed dispersers (Sun et al , Traveset and Richardson ). Invasive species may also benefit from predator or parasite release in the invaded ranges (Van Kleunen et al , Hill and Kotanen , but see Levine et al ), or compete with the native species via the sharing of mutualistic partners (Burns et al , Gibson et al ).…”
Section: ) Integrating Multi‐trophic Interactions Into Invasion Commmentioning
confidence: 99%
“…This is a key result of our study, where it demonstrates that an invasive vector gains fitness benefits in a completely asymptomatic infection. A ‘silent’ infection is particularly threatening as it can allow the pathogen to spread more effectively and go unnoted, and can be particularly problematic when a pathogen-range shifts to regions where the infection becomes symptomatic [22]. It can also contribute to the spread of the invasive vector and potentially other invasive pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…WBDL is a devastating disease, which has spread across the Middle East and resulted in the destruction of more than 50% of the cultivated lime area and 75% loss in production [19,20]. Yet our understanding of this pathosystem and its extent remains limited; WBDL appears to be restricted to the Middle East [17], but with the invasive nature of these vectors [14,21], there is a strong likelihood that these pathogens and pests will increase in importance in other lime markets [22,23]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation